Uncertain execution in order-driven markets - Sanchez Betancourt, L (2021)
So-called 'latency' refers to the various small but significant time delays that occur in the course of the communications between a trader and a market. Such delays happen between the time an exchange streams market data to a trader, the time at which the trader processes the information and decides to trade, and the time at which the exchange receives and processes the order from the trader. Latency is a challenge faced by all traders and is of great importance in modern financial markets. In the present work, we develop mathematical models to solve a variety of problems faced by liquidity takers regarding uncertainty in executions.